Risks of obesity in adolescence : the role of physical activity in executive functions - Gameiro, Fátima (2021)
The aim of this study was to analyze the efficiency of a physical activity program on executive performance in obese adolescents. Fifteen adolescents (5 males and 10 females), with a mean age of 14.73 years and an IMC mean of 36.74 participated in the study. None of the participants presented a compulsive eating disorder when screened by the Binge Eating Scale. A pretest and posttest assessment, twelve months later, was conducted by using a neuropsychological battery that evaluated the cognitive flexibility (Comprehensive Trail Making Test), inhibition control (Stroop Neuropsychological Screening Test and by the Frontal Assessment Battery), and planning (Tower of London). ANOVA of repeated measures was performed. The within-subjects tests demonstrated significant statistical differences between the two moments of evaluation at the level of inhibitory control and cognitive flexibility tasks, with higher performances in the second evaluation. These results suggest that the inclusion of obese adolescents in such programs may promote their executive capacities.